2022
DOI: 10.1021/acs.analchem.1c05142
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Effects Enter Semiconductor-Based SERS: Multiresonant MoO3·xH2O Quantum Dots Enabling Direct, Sensitive SERS Detection of Small Inorganic Molecules

Abstract: There is keen research interest in building highly effective semiconductor-based surface-enhanced Raman scattering (SERS) platforms, due to their selectivity for many probe molecules and suitability for complex scenario applications. However, current tuning approaches have not yet been successful in creating semiconductor-based SERS sensors for small inorganic molecules, due to the challenge of creating sufficient SERS enhancement in semiconductors. Here, we demonstrate the use of MoO 3 •xH 2 O quantum dots (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[ 24 ] This is another evidence of CM mechanism induced by the CT process due to the Herzberg−Teller coupling term. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] This is another evidence of CM mechanism induced by the CT process due to the Herzberg−Teller coupling term. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…[24] This is another evidence of CM mechanism induced by the CT process due to the Herzberg−Teller coupling term. [25] To clarified aerogels effect in SERS activity, a series of experiments were conducted. First of all, the SERS effect of TiO 2 -a1 aerogels was also examined under 633 nm (1.95 eV) and 785 nm (1.58 eV) laser excitation, further shown very weak SERS signal (Figure 3c).…”
Section: Aerogel-based Sersmentioning
confidence: 99%
“…The active utilization of organic semiconductors was inspired by the electronic properties of inorganic semiconductors (ZnO, TiO 2 , lnAs/GaAs, graphene, and CuTe) studied by Usta and Demirel. [110,157] They showed that p-type benzothiophene-based polymer 2,7-dioctyl [1]benzothieno[3,2-b]- [1]benzothiophene (C8-BTBT) in combination with Au thin film could be an efficient plasmonic heterostructure (Figure 14d-1). [106] C8-BTBT was deposited on a Si wafer by chemical vapor deposition followed by sputtering of an Au nanolayer.…”
Section: Large Molecular Structuresmentioning
confidence: 99%
“…Therefore, it is of great significance to develop efficient and sensitive detection methods. As a fast and effective spectroscopic technique, SERS features the capability of detecting the vibrational fingerprints of trace molecules 4,5 The excellent performance promotes its wide-spread application in different fields, such as biological, pharmaceutical, contaminant, and toxin detection fields. [6][7][8] It is imperative to design SERS substrates with high performance for the trace detection of PAAB.…”
Section: Introductionmentioning
confidence: 99%